Correlates of Repeat Victimization and Sex Differences in South Korean Youth. Issue 17 (September 2020) - Lee, Bora; Jo, Youngoh
Interest in the correlates of victimization has significantly increased in criminology, while focusing on a few criminological theories, risky lifestyles/routine activities, and self-control. This study is to explore the applicability of five criminological theories, including social control theory, collective efficacy, and strain theories as well as risky lifestyles/routine activities and self-control to explain the correlates of repeat victimization. The current study also explores sex differences/similarities of Korean youth in the correlates of repeat victimization. Current study analyzes data from two waves of Korean Youth Panel Survey by using logistic regression. Results show that risky lifestyle/routine activities, social control, and general strain variables better explained the chance of repeat victimization than other theories (i.e., self-control and collective efficacy). In addition, this study suggests future study to focus on peer-related issues for girls' repeat victimization and by addressing family-related issues for boys' repeat victimization.